2018
DOI: 10.1093/jae/ejx043
|View full text |Cite
|
Sign up to set email alerts
|

Microcredit and Food Security: Evidence from Rural Households in Uganda

Abstract: This study investigates the effect of participation into a microcredit program on household food security parameters of female borrowers in a rural setting in Uganda. We explore the modes of food acquisition, dietary diversity, caloric and protein intake, and qualitative food insecurity measures for different categories of respondents. We conduct a cross-sectional analysis comparing old clients to newly registered first time borrowers. Next, we compare first time borrowers and non-borrowers using a panel desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“… 41 In a Ugandan study, results showed a decline in food security following the uptake of microcredit. 42 Studies demonstrate that microcredit has had positive impacts on 3 important sectors of national development: the alleviation of poverty, the empowerment of women and food security. 43 The effect of microcredit participation on food security may be non-linear in which participation initially has either no effect on food security or may actually worsen it before improving it in the longer run.…”
Section: Discussionmentioning
confidence: 99%
“… 41 In a Ugandan study, results showed a decline in food security following the uptake of microcredit. 42 Studies demonstrate that microcredit has had positive impacts on 3 important sectors of national development: the alleviation of poverty, the empowerment of women and food security. 43 The effect of microcredit participation on food security may be non-linear in which participation initially has either no effect on food security or may actually worsen it before improving it in the longer run.…”
Section: Discussionmentioning
confidence: 99%
“…By applying the Tobit regression technique, Loibl et al (2017) demonstrated that children's food insecurity was recorded higher in families who had payday loans or pawn shop loans and in families who participated in the Individual Development Account (IDA) than the general population. Along with this, Namayengo et al (2018) with the Difference in Difference (DiD) technique concluded that food security decreased after households took credit. This could be caused by the households having difficulty in paying off the credit installment which later forced them to reduce their consumption (Augsburg et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…By applying instrumental variable techniques, Annim & Frempong (2018) concluded that access to credit contributes to an increase in the diversity of food consumed by households. On the other hand, research by Loibl et al (2017) in the United States and Namayengo et al (2018) in rural Uganda concluded a negative relationship between financial inclusion and food security. By applying the Tobit regression technique, Loibl et al (2017) demonstrated that children's food insecurity was recorded higher in families who had payday loans or pawn shop loans and in families who participated in the Individual Development Account (IDA) than the general population.…”
Section: Introductionmentioning
confidence: 99%